Perovskite ultrathin graphite phase carbon nitride heterojunction photocatalyst as well as preparation method and application thereof
Through the preparation of perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst, the problems of slow carrier transmission and heavy metal pollution in the existing Z-type photocatalytic system are solved, and low-cost, low-pollution high-efficiency light is achieved Catalytic decomposition of water and organic pollutants degradation effect.
Patent Information
- Application Number
- CN202411258117.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The existing Z-type photocatalytic system has slow carrier transmission and low driving force for oxidation/reduction reactions during the total decomposition process. Due to the content of transition metals, the preparation cost is high and it is easy to cause heavy metal contamination, which limits its application potential.
Perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst is prepared by ball milling of boron-doped nitrogen-deficient graphite phase carbon nitride, dimethylamine hydrobromic acid and tin source under an inert gas to form excellent light The heterojunction structure with catalytic properties avoids heavy metal contamination and reduces preparation costs.
The preparation of a low-cost, low-pollution perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst has been achieved, with excellent photocatalytic decomposition properties, stable storage, suitable for large-scale production, and in artificial photosynthesis and organic pollution High efficiency is shown in substance degradation.
Smart Images

Figure HDA0005034705010000011 
Figure HDA0005034705010000012 
Figure HDA0005034705010000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalysis, and in particular relates to a perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst and a preparation method and application thereof. Background Art
[0002] Inspired by natural photosynthesis, the semiconductor-based Z-type heterojunction system is considered to be one of the most effective systems for achieving photocatalytic water splitting. This system consists of two semiconductors with matching energy band structures, in which the semiconductor with a lower conduction band potential is used for photocatalytic hydrogen production, and the semiconductor with a higher valence band potential is used for photocatalytic oxygen production. The carriers are directed through the interface where the two are combined, and the overall orderly oxidation / reduction reaction cycle is achieved. This Z-type system divides the water splitting process into two steps, overcoming the kinetic and thermodynamic bottlenecks of a single semiconductor photocatalyst in the process of complete water splitting, and has therefore been widely studied. So far, a variety of Z-type photocatalytic systems have been successfully developed, such as strontium titanate / bismuth vanadate (J.Am.Chem.Soc.2017,139,1675-1683), strontium titanate / tungsten trioxide (J.Phys.Chem.C2017,121,9691-9697), tantalum nitride / tungsten trioxide (Chem.Sci.2017,8,437-443), metal sulfide / titanium dioxide (J.Am.Chem.Soc.2015,137,604-607), black phosphorus / bismuth vanadate (Angew.Chem.Int.Ed.2018,57,2160-2164), etc. These Z-type systems have a certain ability to fully decompose water, but due to the problems of slow carrier transport and low driving force of oxidation / reduction reactions, the performance of fully decomposing water still needs to be improved. In addition, most of these Z-type systems contain transition metals, which often have high preparation costs and are prone to heavy metal pollution. Therefore, in the field of photocatalytic water splitting, the Z-type system composed of abundant non-metallic elements has gradually shown great potential and attracted great research interest. Summary of the invention
[0003] In order to overcome the problems of high cost and metal pollution in the prior art of using transition metals to prepare Z-type systems, the purpose of the present invention is to provide a low-cost, large-scale production-suitable perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst and a preparation method and application. The preparation cost of this method is low and the method does not contain heavy metals.
[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0005] A method for preparing a perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst comprises the following steps:
[0006] Under an inert gas, boron-doped nitrogen-deficient graphite phase carbon nitride, dimethylamine hydrobromic acid and a tin source in a molar ratio of (1-9):(1-9):(1-12) are ball-milled to obtain a perovskite ultrathin graphite phase carbon nitride heterojunction photocatalyst.
[0007] A further improvement of the present invention is that the inert gas is argon, nitrogen or helium.
[0008] A further improvement of the present invention is that the molar ratio of boron-doped nitrogen-deficient graphite phase carbon nitride, dimethylamine hydrobromic acid and tin source is 2:1:1, 1:1:3, 1:1:9, 9:9:1 or 1:1:12.
[0009] A further improvement of the present invention is that the tin source is stannous bromide.
[0010] A further improvement of the present invention is that the rotation speed of the ball mill is 100-400 rpm, the ball milling time is 6-24 hours; and the ball milling is performed by a method of stopping for 0.25-1 hour after ball milling for 0.5-2 hours.
[0011] A further improvement of the present invention is that the boron-doped nitrogen-deficient graphite phase carbon nitride is prepared by the following process:
[0012] After NaBH4 and polymer carbon nitride nanosheets are uniformly mixed, the mixture is calcined at 300-550° C. under an inert gas to obtain boron-doped nitrogen-defective graphite phase carbon nitride.
[0013] A further improvement of the present invention is that the polymer carbon nitride nanosheets are prepared by the following process:
[0014] Calcine melamine, cyanuric acid, urea, biuret or melamine at 450-600° C. for 2-6 hours to obtain graphite phase carbon nitride;
[0015] The graphite phase carbon nitride is added to water, ultrasonicated, centrifuged, and the suspension is freeze-dried to obtain polymer carbon nitride nanosheets.
[0016] A further improvement of the present invention is that the ultrasonic power is 800-1800W, the ultrasonic time is 2-8 hours, and the ultrasonic is carried out by a method of 1-4 seconds of circulation and 1-4 seconds of stopping.
[0017] A perovskite ultrathin graphite phase carbon nitride heterojunction.
[0018] Disclosed is an application of a perovskite ultrathin graphite phase carbon nitride heterojunction in photocatalytic water decomposition, artificial photosynthesis, degradation of organic pollutants or gas oxidation / reduction.
[0019] Compared with the existing technology, the present invention has the following beneficial effects:
[0020] In the present invention, boron-doped nitrogen-deficient graphite phase carbon nitride, dimethylamine hydrobromic acid and tin source are used as raw materials, and the preparation of a photocatalyst with a heterojunction is achieved by ball milling. In the obtained perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst, XRD characterization clearly shows that the perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst retains the characteristic peaks of dimethylamine tin bromide DMASnBr3 and boron-doped nitrogen-deficient graphite phase carbon nitride BDCN. The photocatalyst has excellent photocatalytic water decomposition performance, good dispersibility, and can be stably stored. The entire preparation process can be achieved at room temperature, is simple to operate, has strong controllability, good repeatability, and cheap raw materials with a wide range of sources. No organic solvent is involved in the reaction process, which can avoid environmental pollution to a certain extent, is green, safe and environmentally friendly, and is conducive to large-scale preparation and practical application.
[0021] Furthermore, boron-doped nitrogen-deficient graphite-phase carbon nitride was synthesized by thermal polymerization, and ultrathin polymer carbon nitride nanosheets were synthesized by ultrasound-calcination two-step method, and then boron-doped nitrogen-deficient graphite-phase carbon nitride was synthesized by rapid calcination in an inert gas environment. The preparation method is simple and easy to implement.
[0022] Furthermore, by freeze drying, the perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst has a large specific surface area and excellent dispersibility, which will provide abundant surface active sites for the catalytic reaction and help to obtain higher reaction activity. The entire preparation process of the present invention is simple to operate, has strong controllability, good repeatability, cheap raw materials and a wide range of sources, is green, safe and environmentally friendly, and is suitable for large-scale production.
[0023] Due to the non-toxic properties of carbon nitride, perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalysts can be widely used in photocatalytic water decomposition, artificial photosynthesis, organic pollutant degradation and other fields. 450 When the mass ratio was 1:3, it showed excellent photocatalytic overall water splitting efficiency, with the highest hydrogen and oxygen generation rates reaching 100 and 50 μmol h -1 DMASnBr3 / BDCN 325 When the mass ratio was 1:3, it exhibited excellent photocatalytic phenyl bromination reaction, with the highest hydrogen and 5,5'-dibromo-2,2'-dithiophene generation rates reaching 367 and 351 μmol h -1 DMASnBr3 / BDCN is used to degrade nitro pollutants such as p-nitrophenol. 450 When the mass ratio was 3:1, it showed excellent photocatalytic nitro pollutant degradation efficiency. For 10mmol / L p-nitrophenol simulated liquid, the degradation rate reached 98% in 3 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The data graphs of the ultra-thin perovskite graphite phase carbon nitride heterojunction photocatalyst prepared in Example 1 of the present invention, wherein (a) is a transmission electron microscope image of DMASnBr3; (b) is a transmission electron microscope image of BDCN 325 Transmission electron microscopy image; (c) DMASnBr3 / BDCN 325 Transmission electron microscopy image; (d) DMASnBr3 / BDCN 325 High-resolution transmission electron microscopy image.
[0025] Figure 2 This is the XRD data diagram of the perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst prepared in Examples 1-5 and Examples 8-9 of the present invention.
[0026] Figure 3 The perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst prepared in Examples 1-5 of the present invention under standard AM1.5 light (100 mW cm -2 ) below, where Figure a is DMASnBr3:BDCN t Heterojunction photocatalytic water splitting performance when the ratio is 9:1; Figure b is DMASnBr3:BDCN t Heterojunction photocatalytic water splitting performance when the ratio is 3:1; Figure c is DMASnBr3:BDCN t Heterojunction photocatalytic water splitting performance when the ratio is 1:1; Figure d is DMASnBr3:BDCN t Heterojunction photocatalytic water splitting performance when the ratio is 1:3; Figure e is DMASnBr3:BDCN t Heterojunction photocatalytic water splitting performance when the ratio is 1:9. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0028] The present invention provides a method for preparing a perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst, comprising the following steps:
[0029] S1. Place 2 g of precursor (melamine, cyanuric acid, urea, biuret or melamine, etc.) in a covered alumina crucible made of ceramic, corundum, etc., calcine at 450-600°C in air for 2-6 hours at a heating rate of 2-10°C / min, and after cooling to room temperature, obtain yellow blocky graphite phase carbon nitride, i.e. PCN, which is crushed.
[0030] 0.05-5 g PCN is added to 40-4000 mL deionized water, stirred for 6 hours under high-power ultrasound and then centrifuged, and the suspension is freeze-dried for 24-72 hours to obtain solid A; wherein the power of the high-power ultrasound is 800-1800 W, the stirring time is 2-8 hours, and the stirring is performed by a 1-4 second cycle and a 1-4 second stop method.
[0031] S2, 0.04-1.6g NaBH4 and 0.1-4g solid A are mixed and ground, then heated to 300-550°C at a heating rate of 10-50°C / s in an inert gas (nitrogen) environment, and calcined for 0.5-2 hours. After cooling to room temperature, the powder is filtered and washed with ethanol and deionized water for multiple times to remove unreacted NaBH4. The powder is freeze-dried for 24-72 hours to obtain boron-doped nitrogen-deficient graphite carbon nitride, i.e., solid B, denoted as BDCN. t , wherein t is the calcination temperature, for example, the calcination temperature is 450°C.
[0032] S3, in an inert gas (argon, nitrogen or helium) environment, solid B, DMABr (dimethylamine hydrobromic acid) and SnBr2 in a molar ratio of (1-9): (1-9): (1-12) (preferably 2:1:1, 1:1:3, 1:1:9, 9:9:1 or 1:1:12) are placed in a tank, and ground by ball milling to obtain the target product, perovskite ultrathin graphite phase carbon nitride heterojunction photocatalyst, denoted as DMASnBr3 / BDCN t , where t is the calcination temperature. The ball milling method uses a rotation speed of 100-400 rpm, a grinding time of 6-24 hours, a grinding time of 0.5-2 hours and a stopping time of 0.25-1 hours, and a ball / reagent mass ratio of 1:40.
[0033] The perovskite ultra-thin graphite phase carbon nitride heterojunction prepared by the method has excellent photocatalytic water decomposition performance, and the highest hydrogen and oxygen generation rates reach 100 and 50 μmol h -1 , good dispersibility in water, and can be stably stored for 1-2 years. The whole preparation process of the invention is simple to operate, has strong controllability, good repeatability, cheap raw materials and a wide range of sources, and is green, safe and can be mass-produced.
[0034] The perovskite ultra-thin graphite phase carbon nitride heterojunction is used in photocatalytic water decomposition, artificial photosynthesis, organic pollutant degradation or gas oxidation / reduction.
[0035] Among them, DMASnBr3 / BDCN 450 When the mass ratio was 1:3, it showed excellent photocatalytic overall water splitting efficiency, with the highest hydrogen and oxygen generation rates reaching 100 and 50 μmol h -1 .
[0036] The invention discloses a method for preparing a perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst. The perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst is prepared by a safe and easy-to-operate three-step ultrasound-calcination-ball milling method. The obtained heterojunction photocatalyst has a novel structure, excellent photocatalytic water decomposition performance, good dispersibility, stable storage, short reaction time, low reaction temperature, simple operation, strong controllability, good repeatability, cheap raw materials and a wide range of sources, green, safe and environmentally friendly, and is conducive to large-scale preparation and practical application. The invention enriches the research field of heterojunction photocatalysts and accumulates valuable experience for the development of efficient photocatalysts.
[0037] The preparation method of the present invention comprises synthesizing bulk PCN by thermal polymerization, synthesizing ultrathin polymerized carbon nitride nanosheets by ultrasound-calcination two-step method, then synthesizing boron-doped and nitrogen-deficient PCN nanosheets by rapid calcination under an inert gas environment, synthesizing DMASnBr3 by ball milling, and finally constructing DMASnBr3 / BDCN by the same ball milling method. t Heterostructure, obtaining perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst.
[0038] The technical details of the present invention are described below in conjunction with the accompanying drawings and several preferred embodiments of the present invention.
[0039] Example 1
[0040] 1) Melamine (2 g) was calcined in an alumina crucible with a lid at 520° C. in air for 4 hours at a heating rate of 5° C. / min. After cooling to room temperature, the yellow blocky PCN obtained was crushed.
[0041] 2) 0.5 g of the pre-prepared block PCN was added to a 500 ml glass beaker containing 400 ml of deionized water. The mixture was stirred under high-power ultrasound (1500 W) for 6 hours (2 seconds cycle, 2 seconds stop). After centrifugation, the resulting suspension was freeze-dried for 48 hours to obtain solid A, weighing about 0.26 g.
[0042] 3) 0.4 g of solid A and 0.16 g of NaBH4 were ground and then calcined at 325°C in nitrogen at a rate of 20°C / s for 1 hour. After cooling to room temperature, the powder was washed several times with ethanol and deionized water to remove unreacted NaBH4. After a 48-hour freeze-drying process, solid B was obtained.
[0043] 4) In an argon environment, solid B, DMABr and SnBr2 were placed in a tank at a mass ratio of 1:1:9, and ground at 300 rpm for 12 hours (1 hour cycle, 30 minutes stop), with a ball / reagent ratio of 1:40 to obtain a perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst. DMASnBr3:BDCN in the perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst t is 9:1, and the property parameters are as follows Figure 3 As shown in c, the maximum hydrogen production rate reached 18 μmol h -1 The oxygen production rate reached a maximum of 8 μmol h -1 .
[0044] Example 2
[0045] 1) Melamine (2 g) was calcined in an alumina crucible with a lid at 520° C. in air for 4 hours at a heating rate of 5° C. / min. After cooling to room temperature, the yellow blocky PCN obtained was crushed.
[0046] 2) 0.5 g of the pre-prepared block PCN was added to a 500 ml glass beaker containing 400 ml of deionized water. The mixture was stirred under high-power ultrasound (1500 W) for 6 hours (2 seconds cycle, 2 seconds stop). After centrifugation, the resulting suspension was freeze-dried for 48 hours to obtain solid A, weighing about 0.26 g.
[0047] 3) 0.4 g of solid A and 0.16 g of NaBH4 were ground and then calcined at 325°C in nitrogen at a rate of 20°C / s for 1 hour. After cooling to room temperature, the powder was washed several times with ethanol and deionized water to remove unreacted NaBH4. After a 48-hour freeze-drying process, solid B was obtained.
[0048] 4) In an argon environment, solid B, DMABr and SnBr2 were placed in a tank at a mass ratio of 1:1:3, and ground at 300 rpm for 12 hours (1 hour cycle, 30 minutes stop), with a ball / reagent ratio of 1:40 to obtain a perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst. DMASnBr3:BDCN in the perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst t is 3:1, and the property parameters are as follows Figure 3 As shown in c, the maximum hydrogen production rate reached 23 μmol h -1The oxygen production rate reached a maximum of 11 μmol h -1 .
[0049] Example 3
[0050] 1) Melamine (2 g) was calcined in an alumina crucible with a lid at 520° C. in air for 4 hours at a heating rate of 5° C. / min. After cooling to room temperature, the yellow blocky PCN obtained was crushed.
[0051] 2) 0.5 g of the pre-prepared block PCN was added to a 500 ml glass beaker containing 400 ml of deionized water. The mixture was stirred under high-power ultrasound (1500 W) for 6 hours (2 seconds cycle, 2 seconds stop). After centrifugation, the resulting suspension was freeze-dried for 48 hours to obtain solid A, weighing about 0.26 g.
[0052] 3) 0.4 g of solid A and 0.16 g of NaBH4 were ground and then calcined at 325°C in nitrogen at a rate of 20°C / s for 1 hour. After cooling to room temperature, the powder was washed several times with ethanol and deionized water to remove unreacted NaBH4. After a 48-hour freeze-drying process, solid B was obtained.
[0053] 4) In an argon environment, solid B, DMABr and SnBr2 were placed in a tank at a mass ratio of 1:1:1, and ground at 300 rpm for 12 hours (1 hour cycle, 30 minutes stop), with a ball / reagent ratio of 1:40 to obtain a perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst. DMASnBr3:BDCN in the perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst t is 1:1, and the property parameters are as follows Figure 3 As shown in c, the maximum hydrogen production rate reaches 50 μmol h -1 The oxygen production rate reached a maximum of 25 μmol h -1 .
[0054] from Figure 1 From (a) to (d), we can see that DMASnBr3 is successfully anchored to BDCN. 325 The grain boundary between the two can be clearly observed by high-resolution transmission electron microscopy.
[0055] Example 4
[0056] 1) Melamine (2 g) was calcined in an alumina crucible with a lid at 520° C. in air for 4 hours at a heating rate of 5° C. / min. After cooling to room temperature, the yellow blocky PCN obtained was crushed.
[0057] 2) 0.5 g of the pre-prepared block PCN was added to a 500 ml glass beaker containing 400 ml of deionized water. The mixture was stirred under high-power ultrasound (1500 W) for 6 hours (2 seconds cycle, 2 seconds stop). After centrifugation, the resulting suspension was freeze-dried for 48 hours to obtain solid A, weighing about 0.26 g.
[0058] 3) 0.4 g of solid A and 0.16 g of NaBH4 were ground and then calcined at 450°C in nitrogen at a rate of 20°C / s for 1 hour. After cooling to room temperature, the powder was washed several times with ethanol and deionized water to remove unreacted NaBH4. After a 48-hour freeze-drying process, solid B was obtained.
[0059] 4) In an argon environment, solid B, DMABr and SnBr2 were placed in a tank in a mass ratio of 1:3:1, and ground at 300 rpm for 12 hours (1 hour cycle, 30 minutes stop), with a ball / reagent ratio of 1:40 to obtain a perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst. The obtained perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst has DMASnBr3:BDCN t is 1:3, and the property parameters are as follows Figure 3 As shown in (d), the maximum hydrogen production rate reached 100 μmol h -1 The oxygen production rate can reach up to 50 μmol / h -1 .
[0060] Example 5
[0061] 1) Melamine (2 g) was calcined in an alumina crucible with a lid at 520° C. in air for 4 hours at a heating rate of 5° C. / min. After cooling to room temperature, the yellow blocky PCN obtained was crushed.
[0062] 2) 0.5 g of the pre-prepared block PCN was added to a 500 ml glass beaker containing 400 ml of deionized water. The mixture was stirred under high-power ultrasound (1500 W) for 6 hours (2 seconds cycle, 2 seconds stop). After centrifugation, the resulting suspension was freeze-dried for 48 hours to obtain solid A, weighing about 0.26 g.
[0063] 3) 0.4 g of solid A and 0.16 g of NaBH4 were ground and then calcined at 500°C in nitrogen at a rate of 20°C / s for 1 hour. After cooling to room temperature, the powder was washed several times with ethanol and deionized water to remove unreacted NaBH4. After a 48-hour freeze-drying process, solid B was obtained.
[0064] 4) In an argon environment, solid B, DMABr and SnBr2 were placed in a tank in a mass ratio of 1:9:1, and ground at 300 rpm for 12 hours (1 hour cycle, 30 minutes stop), with a ball / reagent ratio of 1:40 to obtain a perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst. The obtained perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst has DMASnBr3:BDCN t is 1:9, and the property parameters are Figure 3 As shown in Figure e, the maximum hydrogen production rate reached 58 μmol h -1 The oxygen production rate can reach up to 40 μmol / h -1 .
[0065] Figure 3 a, b, c, d and e are the performance parameter data of the ultra-thin graphite phase carbon nitride heterojunction photocatalyst obtained in Examples 1 to 5. It can be seen that in the ultra-thin graphite phase carbon nitride heterojunction photocatalyst obtained by the present invention, DMASnBr3:BDCN t The heterojunction structure is stable, and the maximum photocatalytic water decomposition hydrogen production rate can reach 100 μmol h -1 , with excellent visible light photocatalytic decomposition of water to produce hydrogen performance.
[0066] Example 6
[0067] 1) Melamine (2 g) was calcined in an alumina crucible with a lid at 520° C. in air for 4 hours at a heating rate of 5° C. / min. After cooling to room temperature, the yellow blocky PCN obtained was crushed.
[0068] 2) 0.5 g of the pre-prepared block PCN was added to a 500 ml glass beaker containing 400 ml of deionized water. The mixture was stirred under high-power ultrasound (1500 W) for 6 hours (2 seconds cycle, 2 seconds stop). After centrifugation, the resulting suspension was freeze-dried for 48 hours to obtain solid A, weighing about 0.26 g.
[0069] 3) 0.4 g of solid A and 0.16 g of NaBH4 were ground and then calcined at 375°C in nitrogen at a rate of 20°C / s for 1 hour. After cooling to room temperature, the powder was washed several times with ethanol and deionized water to remove unreacted NaBH4. After a 48-hour freeze-drying process, solid B was obtained.
[0070] 4) Solid B, DMABr and SnBr2 were charged into a tank in a mass ratio of 9:9:1 under an argon environment, and ground at 300 rpm for 12 hours (1 hour cycle, 30 minutes stop), with a ball / reagent ratio of 1:40, to obtain a perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst.
[0071] Example 7
[0072] 1) Melamine (2 g) was calcined in an alumina crucible with a lid at 520° C. in air for 4 hours at a heating rate of 5° C. / min. After cooling to room temperature, the yellow blocky PCN obtained was crushed.
[0073] 2) 0.5 g of the pre-prepared block PCN was added to a 500 ml glass beaker containing 400 ml of deionized water. The mixture was stirred under high-power ultrasound (1500 W) for 6 hours (2 seconds cycle, 2 seconds stop). After centrifugation, the resulting suspension was freeze-dried for 48 hours to obtain solid A, weighing about 0.26 g.
[0074] 3) 0.4 g of solid A and 0.16 g of NaBH4 were ground and then calcined at 425°C in nitrogen at a rate of 20°C / s for 1 hour. After cooling to room temperature, the powder was washed several times with ethanol and deionized water to remove unreacted NaBH4. After a 48-hour freeze-drying process, solid B was obtained.
[0075] 4) Solid B, DMABr and SnBr2 were charged into a tank in a mass ratio of 1:1:12 under an argon environment, and ground at 300 rpm for 12 hours (1 hour cycle, 30 minutes stop), with a ball / reagent ratio of 1:40, to obtain a perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst.
[0076] Example 8
[0077] 1) Melamine (2 g) was calcined in air at 450° C. for 6 hours in a covered alumina crucible at a heating rate of 2° C. / min. After cooling to room temperature, the yellow blocky PCN obtained was crushed.
[0078] 2) 0.05 g of the previously prepared block PCN was added to a 500 ml glass beaker containing 40 ml of deionized water. The mixture was stirred under high power ultrasound (1500 W) for 2 hours (1 second cycle, 1 second stop). After centrifugation, the resulting suspension was freeze dried for 24 hours to obtain solid A, weighing about 0.26 g.
[0079] 3) 0.04 g of solid A and 0.1 g of NaBH4 were ground and then calcined at 300°C in nitrogen at a rate of 10°C / s for 2 hours. After cooling to room temperature, the powder was washed several times with ethanol and deionized water to remove unreacted NaBH4. After a 48-hour freeze-drying process, solid B was obtained.
[0080] 4) Solid B, DMABr and SnBr2 were charged into a tank in a mass ratio of 2:1:1 under an argon environment, and ground at a speed of 100 rpm for 6 hours (0.5 hour cycle, 60 minute stop), with a ball / reagent ratio of 1:40, to obtain a perovskite ultrathin graphite phase carbon nitride heterojunction photocatalyst.
[0081] Example 9
[0082] 1) Melamine (2 g) was calcined in air at 600° C. for 2 hours in a covered alumina crucible at a heating rate of 10° C. / min. After cooling to room temperature, the yellow blocky PCN was crushed.
[0083] 2) 5 g of the pre-prepared block PCN was added to a 500 ml glass beaker containing 400 ml of deionized water. The mixture was stirred under high-power ultrasound (1500 W) for 8 hours (4 seconds cycle, 4 seconds stop). After centrifugation, the resulting suspension was freeze-dried for 72 hours to obtain solid A, weighing about 0.26 g.
[0084] 3) 0.1 g of solid A and 1 g of NaBH4 were ground and then calcined at 550°C in nitrogen at a rate of 30°C / s for 0.5 h. After cooling to room temperature, the powder was washed several times with ethanol and deionized water to remove unreacted NaBH4. After a 48-hour freeze-drying process, solid B was obtained.
[0085] 4) Solid B, DMABr and SnBr2 were charged into a tank in a mass ratio of 5:3:10 under an argon environment, and ground at 400 rpm for 24 hours (1 hour cycle, 25 minutes stop), with a ball / reagent ratio of 1:40, to obtain a perovskite ultrathin graphite phase carbon nitride heterojunction photocatalyst.
[0086] Example 10
[0087] 1) Melamine (2 g) was calcined in an alumina crucible with a lid at 500° C. in air for 4 hours at a heating rate of 7° C. / min. After cooling to room temperature, the yellow blocky PCN obtained was crushed.
[0088] 2) 2 g of the pre-prepared block PCN was added to a 500 ml glass beaker containing 200 ml of deionized water. The mixture was stirred under high-power ultrasound (1500 W) for 5 hours (3 seconds cycle, 3 seconds stop). After centrifugation, the resulting suspension was freeze-dried for 60 hours to obtain solid A, weighing about 0.26 g.
[0089] 3) 1.6 g of solid A and 4 g of NaBH4 were ground and then calcined at 400°C in nitrogen at a rate of 50°C / s for 1 hour. After cooling to room temperature, the powder was washed several times with ethanol and deionized water to remove unreacted NaBH4. After a 48-hour freeze-drying process, solid B was obtained.
[0090] 4) Solid B, DMABr and SnBr2 were charged into a tank in a mass ratio of 7:2:5 under an argon environment, and ground at 200 rpm for 20 hours (2-hour cycle, 30-minute stop), with a ball / reagent ratio of 1:40, to obtain a perovskite ultrathin graphite phase carbon nitride heterojunction photocatalyst.
[0091] Embodiment 11
[0092] Same as Example 1, except that, in step 3), 1.6 g of solid A and 4 g of NaBH4 were ground and then calcined at 350°C at a rate of 40°C / s in nitrogen for 1 hour. After cooling to room temperature, the powder was washed with ethanol and deionized water several times to remove unreacted NaBH4. After 48 hours of freeze drying, solid B was obtained.
[0093] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.
[0094] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
Claims
1. A method for preparing a perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst, characterized in that: The following steps are involved: Under an inert gas, boron-doped nitrogen-deficient graphite phase carbon nitride, dimethylamine hydrobromic acid and a tin source in a molar ratio of (1-9):(1-9):(1-12) are ball-milled to obtain a perovskite ultrathin graphite phase carbon nitride heterojunction photocatalyst.
2. The method for preparing the ultra-thin perovskite graphite phase carbon nitride heterojunction photocatalyst according to claim 1, characterized in that: The inert gas is argon, nitrogen or helium.
3. The method for preparing the perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst according to claim 1, characterized in that: The molar ratio of boron-doped nitrogen-deficient graphite phase carbon nitride, dimethylamine hydrobromic acid and tin source is 2:1:1, 1:1:3, 1:1:9, 9:9:1 or 1:1:
12.
4. The method for preparing the perovskite ultra-thin graphite phase carbon nitride heterojunction photocatalyst according to claim 1, characterized in that: The tin source is stannous bromide.
5. The method for preparing the ultra-thin perovskite graphite phase carbon nitride heterojunction photocatalyst according to claim 1, characterized in that: The rotation speed of the ball mill is 100-400 rpm, and the ball milling time is 6-24 hours; the ball milling is performed by a method of stopping for 0.25-1 hour after ball milling for 0.5-2 hours.
6. The method for preparing the ultra-thin perovskite graphite phase carbon nitride heterojunction photocatalyst according to claim 1, characterized in that: Boron-doped nitrogen-deficient graphite phase carbon nitride is prepared by the following process: After NaBH4 and polymer carbon nitride nanosheets are uniformly mixed, the mixture is calcined at 300-550° C. under an inert gas to obtain boron-doped nitrogen-defective graphite phase carbon nitride.
7. The method for preparing the ultra-thin perovskite graphite phase carbon nitride heterojunction photocatalyst according to claim 6, characterized in that: Polymer carbon nitride nanosheets are prepared by the following process: Calcine melamine, cyanuric acid, urea, biuret or melamine at 450-600° C. for 2-6 hours to obtain graphite phase carbon nitride; The graphite phase carbon nitride is added to water, ultrasonicated, centrifuged, and the suspension is freeze-dried to obtain polymer carbon nitride nanosheets.
8. The method for preparing the ultra-thin perovskite graphite phase carbon nitride heterojunction photocatalyst according to claim 7, characterized in that: The ultrasonic power is 800-1800W, the ultrasonic time is 2-8 hours, and the ultrasonic is performed by a 1-4 second cycle and a 1-4 second stop method.
9. A perovskite ultra-thin graphite phase carbon nitride heterojunction prepared according to the method according to any one of claims 1 to 8.
10. An application of the perovskite ultra-thin graphite phase carbon nitride heterojunction prepared by the method according to any one of claims 1 to 8 in photocatalytic water decomposition, artificial photosynthesis, degradation of organic pollutants or gas oxidation / reduction.
Citation Information
Patent Citations
Preparation method and application of amorphous boron-doped carbon nitride
CN115007194A
Boron-doped graphite phase carbon nitride as well as preparation method and application thereof
CN116571265A
Preparation and application of ultrathin B-doped carbon nitride photocatalyst
CN118594593A
